Simulation and analysis of thermal behavior of a computer room in a warm-humid zone: Collaboration with the XXIII Peruvian Symposium on Solar Energy - Mendoza Vela, Dora (2020)
The objective of this paper is to know the thermal behavior of a computer room in different class. It is located at University Headquarters in the city of Orán (Province of Salta, Argentina), a place characterized by having a warm-humid climate. The simulation is carried out for 10 days and coincides with the class period, using data from National Meteorological Service and on-site measurements. The simulation software used is SIMEDIF. The work methodology includes recognition activities, measuring, data and scenes preparation, simulation and analysis of results. From the results obtained, uncomfortable situations are detected and thermal load required to overcome them is calculated. It is necessary to incorporate bioclimatic and passive cooling strategies in order to achieve hygro-thermal comfort with minimum energy consumption and minimum environmental impact. The importance of the work lies in obtaining a first approximation to the real thermal behavior of an environment through modeling and simulation with computational tools.